AMALAN PEMBAHAGIAN HARTA SEPENCARIAN DI MALAYSIA: SATU SOROTAN LITERATUR - Mat Hussin, Mohd Norhusairi (Journal of Shariah Law Research, 2017)
One of the particular predicaments of the cases arising out of divorce is the settlement of the distribution of Harta Sepencarian, the subject of this research. There has been a lot of academic works that has addressed in Malaysia, but not many of the discussions are written from socio legal in Malaysia. This article discusses the methods for determining contribution of Harta Sepencarian from socio legal aspects in Malaysia. It includes an analysis of contributions that are recognized by the court in deciding Harta Sepencarian cases. To achieve this objective, there are two sources from where the cases are taken. The first source is from Jurnal Hukum between year 1980 to 2010. The second source is the unreported cases of the Shariah Court in Malaysia from the year 2006-2010 from five selected states namely Kuala Lumpur, Negeri Sembilan, Kelantan, Kedah and Sabah. Through analysis, the article also examines types of properties that are usually claimed in the court, the concept of contribution as well as the judicial process in determining the distribution of Harta Sepencarian. Although the term â€œcontributionâ€ has been defined by the court to include financial support, household management, energy and effort, it also encompasses the duration of marriage of a couple, and if husband has provided the wife a maid during the marriage. The article found that the ratio decided by the court in determining the distribution of Harta Sepencarian are usually parallel with the extended of contributions by the parties. Once the above issues have been considered, the thesis has found that â€œsulá¸¥â€ has been widely used by the court in resolving the disputes of the parties in Harta Sepencarian cases.